Biogeochemical sediment core data from Lake Rzesniki, NE Poland - Giulia Wienhues; Hendrik Vogel; Wojciech Tylmann; Martin Grosjean (PANGAEA, 2025)
This dataset comprises high-resolution biogeochemical data from a sediment core retrieved from Lake Rzęśniki, located in Northeastern Poland. The multi-proxy record integrates X-ray fluorescence (XRF) elemental data, hyperspectral imaging (HSI), sedimentary pigment concentrations, and Fourier-transform infrared spectroscopy (FTIRS)-derived biogenic silica measurements. Together, these proxies provide a detailed reconstruction of past environmental and limnological conditions. The sediment core has been chronologically constrained using radiocarbon dating, allowing for temporal interpretation of biogeochemical changes throughout the Holocene. This dataset offers valuable insights for regional paleoclimate reconstructions, ecological change assessments, and comparative studies across the Northern European lowlands.